Evolving ethics, policy and reimbursement issues of vascularized composite allotransplantation: Symposium summary. (July 2019) - Rose, John; Cooney, Carisa M; Kaufman, Christina; Talbot, Simon G; Caplan, Arthur; Kahn, Jeffrey; Sugarman, Jeremy; Shores, Jaimie T; Levin, L Scott; Brandacher, Gerald; McDiarmid, Sue V; Lee, WP Andrew; et al.
In this article, we present a report from a national meeting titled, "Evolving Issues of Vascularized Composite Allotransplantation—A Symposium on Ethics, Policy, and Reimbursement Issues, " which convened in September 2017. We discuss the maturation of vascularized composite allotransplantation from an emerging technology to becoming an extension of clinical practice for select patients with complex reconstructive needs. Viewpoints and action items were presented by and discussed among the 70+ clinicians, researchers, policymakers, ethicists, healthcare administrators, and third-party payers who attended the symposium with the goals of implementing a collaborative roadmap for vascularized composite allotransplantation growth, evaluation, and sustainability by establishing a unified plan to help address concerns of the public, policymakers, and healthcare finance. We review the current status of vascularized composite allotransplantation in clinical practice and summarize symposium discussions regarding ethical considerations, reimbursement, payer strategies, and standardization of data collection.